The Effect of Finishing and Polishing Systems on Surface Roughness and Microbial Adhesion of Bulk Fill Composites: A Systematic Review and Meta-analysis - Hoda Saleh Ismail; Ashraf Ibrahim Ali (Tehran University of Medical Sciences, 2023)
Objectives: This paper presents a systematic review and meta-analysis of the effect of different finishing and polishing (F/P) systems on surface roughness (SR) and microbial adhesion to bulk fill (BF) composites. Materials and Methods: An electronic search of 3 databases (the National Library of Medicine [MEDLINE/PubMed], Scopus, and ScienceDirect) was conducted. Only in vitro studies that evaluated SR and microbial adhesion to BF composites were included. The included studies were individually evaluated for the risk of bias following predetermined criteria. A meta-analysis of the reviewed studies was conducted to compare the SR values of both Filtek Bulk Fill and Tetric EvoCeram Bulk Fill with and without F/P using the Comprehensive Meta-Analysis software. Results: A total of 12 studies fulfilled the inclusion criteria. The meta-analysis showed no significant difference between Filtek Bulk Fill and Tetric EvoCeram Bulk Fill without F/P or after F/P using multi-step systems. Different F/P systems affected the SR values, on the other hand, did not affect microbial adhesion values. Conclusion: Both Filtek Bulk Fill and Tetric EvoCeram Bulk Fill had comparable roughness results. Multi-step systems may be preferable for F/P of BF composites.